Absorbing phase transition in a parity-conserving particle process on a Sierpinski carpet fractal. (2nd September 2019) - Argolo, C; Tenório, V; Gleria, Iram
Abstract: We study a stochastic lattice model with parity-conserving particle process using a Monte Carlo procedure. We perform simulations on a Sierpinski carpet fractal with dimension . We calculate the critical exponents at the threshold of the absorbing phase transition at the known value for the critical diffusion p c = 1 (Cardy and Tauber 1996 Phys. Rev. Lett . 77 4780). Using finite-size and finite-time scaling analysis we calculate the critical exponents at p c = 1 and below, where a finite density of particles is found in the long-time limit. From dynamic simulations we calculate the dynamical exponents Z, , , and, and they are found to differ from the mean-field values, as well as the stationary exponent . We check the consistence of the results with the hyperscaling relation.